Students’ views of using REVERSO.NET in learning Arabic vocabulary among non-native speakers = آراء الطلاب في استخدام ريفرسو.نت (REVERSO.NET) لتعلم مفردات العربية لدى الناطقين بغيرها - Abu Bakar, Radhwa; Hassan, Nursyakirah (USULI FAQIH RESEARCH CENTRE PLT, 2020)
Many problems arose, including the phenomenon of a lack of vocabulary among foreign language learners, especially Arabic. They face difficulty remembering and using them when speaking or writing in addition to they need language tools from Internet to help them facilitate their studies. The aim of this study is to investigate the students’ views in learning Arabic vocabulary towards Reverso.net. This study is chose stratified sampling which is involved 30 respondents from Department of Arabic Language, IIUM. The instrument of this study is a quantitative means, using a questionnaire containing 27 items which are based on four objectives; to know the extent which they use Reverso.net, their perspectives on its features, level of satisfaction in learning Arabic vocabulary and how their relationship. Data was analysed using Statistical Package of Social Science (SPSS) for Windows version 22.0 to find frequency, percentage, mean, standard deviation and Pearson Correlation descriptively. Cronbach Alpha reliability coefficient value for the instrument was 0.85. The result shows that the overall perception of the student in learning Arabic vocabulary towards Reverso.net is high and positively related each other among its features and the level of their satisfaction using Reverso.net.